Circadian misalignment and weekend alcohol use in late adolescent drinkers: preliminary evidence. (3rd June 2019) - Hasler, Brant P.; Bruce, Scott; Scharf, Deborah; Ngari, Wambui; Clark, Duncan B.
ABSTRACT: Alcohol use accelerates during late adolescence, predicting the development of alcohol use disorders (AUDs) and other negative outcomes. Identifying modifiable risk factors for alcohol use during this time could lead to novel prevention approaches. Burgeoning evidence suggests that sleep and circadian factors are cross-sectionally and longitudinally linked to alcohol use and problems, but more proximal relationships have been understudied. Circadian misalignment, in particular, is hypothesized to increase the risk for AUDs, but almost no published studies have included a biological measure of misalignment. In the present study, we aimed to extend existing research by assessing the relationship between adolescent circadian misalignment and alcohol use on a proximal timeframe (over two weeks) and by including three complementary measures of circadian alignment. We studied 36 healthy late (18–22 years old, 22 females) alcohol drinkers (reporting ≥1, standard drink per week over the past 30 days) over 14 days. Throughout the study, participants reported prior day's alcohol use and prior night's sleep each morning via smartphone and a secure, browser-based interface. Circadian phase was assessed via the dim light melatonin onset (DLMO) in the laboratory on two occasions (Thursday and Sunday nights) in counterbalanced order. The three measures of circadian alignment included DLMO-midsleep interval, "classic" social jet lag (weekday-weekend difference in midsleep), and "objective" social jet lag (weekday-weekend difference in DLMO). Multivariate imputation by chained equations was used to impute missing data, and Poisson regression models were used to assess associations between circadian alignment variables and weekend alcohol use. Covariates included sex, age, Thursday alcohol use, and Thursday sleep characteristics. As predicted, greater misalignment was associated with greater weekend alcohol use for two of the three alignment measures (shorter DLMO-midsleep intervals and larger weekday-weekend differences in midsleep), while larger weekday-weekend differences in DLMO were associated with less alcohol use. Notably, in contrast to expectations, the distribution of weekday-weekend differences in DLMO was nearly equally distributed between individuals advancing over the weekend and those delaying over the weekend. This unexpected finding plausibly reflects the fact that college students are not subject to the same systematically earlier weekday schedules observed in high school students and working adults. These preliminary findings support the need for larger, more definitive studies investigating the proximal relationships between circadian alignment and alcohol use among late adolescents.